2023
DOI: 10.21037/tau-22-743
|View full text |Cite
|
Sign up to set email alerts
|

ALDOB represents a potential prognostic biomarker for patients with clear cell renal cell carcinoma

Abstract: Background Previous studies have shown that aldolase B (ALDOB) might play controversial roles in multiple types of cancer, which could act as a cancer-promoting factor or a cancer-inhibiting factor depending on the subtype of the cancer. However, the role of ALDOB in clear cell renal cell carcinoma (ccRCC) patients has not been clearly elucidated. Therefore, this study aimed to comprehensively explore the expression level, prognostic value, functional enrichment, immune infiltration, and N6-methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…Among the 11 GRGs examined, GPI is a predictor of outcomes in UCEC patients [36][37][38] as well as other cancers [39][40][41][42] . Similarly, other genes such as HK1 43,44 , PDHA1 [45][46][47] , PGK2 48 , NUP155 49 , PC [50][51][52] , ALDOB [53][54][55][56] , and PFKM 57,58 have been implicated in carcinogenesis and have demonstrated effects on patient prognoses in various cancer types. We observed that PDHA1 and GPI exhibit the highest positive correlation.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 11 GRGs examined, GPI is a predictor of outcomes in UCEC patients [36][37][38] as well as other cancers [39][40][41][42] . Similarly, other genes such as HK1 43,44 , PDHA1 [45][46][47] , PGK2 48 , NUP155 49 , PC [50][51][52] , ALDOB [53][54][55][56] , and PFKM 57,58 have been implicated in carcinogenesis and have demonstrated effects on patient prognoses in various cancer types. We observed that PDHA1 and GPI exhibit the highest positive correlation.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al ( 11 ) found SPOCK1 participates in the epithelial-mesenchymal transition process and may be a potential prognostic biomarker in ccRCC. Shao et al ( 12 ) found that the down-regulation of ALDOB was closely related to the clinicopathological features, poor prognosis, immune infiltration and m6A modification of ccRCC patients by integrating multiple public databases. Liao et al ( 13 ) established a survival and prognosis model system by exploring immune-related genes, and provided an effective prediction tool for the future.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, a plethora of studies has been dedicated to exploring potential prognostic biomarkers for ccRCC. Notably, some investigations have revealed that ccRCC patients exhibiting low expression of ALDOB ( 11 ), high expression of p-CREB1 ( 12 ), or elevated expression of SPOCK1 ( 13 ) are associated with a less favorable prognosis. However, the association between deoxyribonuclease 1 like 3 (DNASE1L3) and ccRCC remains unexplored.…”
Section: Introductionmentioning
confidence: 99%